2010
DOI: 10.4314/tjpr.v8i6.49392
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Equivalence of Some Commercial Samples of Artesunate and Amodiaquine Tablets Sold in Southwestern Nigeria

Abstract: Purpose: To study the physical properties and dissolution profiles of commercial samples of artesunate and amodiaquine tablets. Methods: Fifteen generic brands of artesunate and five generic brands of amodiaquine tablets were obtained from drug retail outlets in Oyo and Ogun States in southwestern Nigeria. The tablets were subjected to various compendial tests including identification, weight uniformity, uniformity of content, content of active ingredient and uniformity of diameter. Additional tests used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…References standards are pure chemical compounds obtained from chemical manufacturing companies and are used by pharmacopeia such as USP as a basis for their official monographs for analysts to adopt. This review found that 15/39 (39%) studies stated using reference standards in the analytical process and reported on the source of the standard [ 30 , 35 , 38 42 , 45 , 46 , 49 , 65 , 67 , 76 , 78 , 79 ]. Of the 35/39 (89.7%) studies (excluding those that conducted visual inspection alone), 10/35 (29%) did not mention the source of the screening tests (and reagents), but simply named the device they were utilizing; MiniLab ® or a Raman handheld device [ 28 – 32 , 42 , 45 , 48 , 51 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…References standards are pure chemical compounds obtained from chemical manufacturing companies and are used by pharmacopeia such as USP as a basis for their official monographs for analysts to adopt. This review found that 15/39 (39%) studies stated using reference standards in the analytical process and reported on the source of the standard [ 30 , 35 , 38 42 , 45 , 46 , 49 , 65 , 67 , 76 , 78 , 79 ]. Of the 35/39 (89.7%) studies (excluding those that conducted visual inspection alone), 10/35 (29%) did not mention the source of the screening tests (and reagents), but simply named the device they were utilizing; MiniLab ® or a Raman handheld device [ 28 – 32 , 42 , 45 , 48 , 51 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…A second operator to independently verify test results would enhance the validity of a study by minimizing the risk of operator error in results interpretation, particularly for the semi-quantitative TLC test in which there is a greater risk of misclassification bias. Overall, 31 studies used TLC, but only three reported using a second operator to verify results [ 38 , 69 , 75 ]. For 8/39 (21%) studies using visual inspection and/or colorimetry, a second operator would be unnecessary as results are more definitive in comparison to TLC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A intercambialidade entre os medicamentos Genéricos e de Referência tem sido amplamente discutida em publicações científicas (4)(5)(6)(7)(8). Storpirtis e cols.…”
Section: Introductionunclassified